Ancestry informative markers: A foundation for unravelling genetic ancestry and population structures - Akanksha Chaudhary; Nidhishree N.S; Rakesh Kumar Pundir; Amod Kumar (Journal of Livestock Biodiversity, 2025)
Deciphering the genetic ancestry in livestock species has important applications in population stratification and is to used explore the genetic basis for differences among the breeds within the populations. Genetic ancestry plays a crucial role in identifying population structure by determining the number of subpopulations within a population and assigning individuals to their respective groups. It is also instrumental in defining the number of ancestral populations in admixed populations and estimating the proportions of these ancestral populations in admixed individuals. The study of Ancestry Informative Markers (AIMs) has significantly advanced our understanding of genetic variation within populations, with applications ranging from anthropology to livestock management. AIMs are specific genetic markers, such as SNPs, that show significant allele frequency differences between populations, allowing researchers to trace lineage and analyse population structure. With the advent of next-generation sequencing technologies and SNP genotyping, AIMs have become invaluable for uncovering the biogeographical origins of species, aiding in conservation efforts, and improving livestock breeding strategies. In this review, we have briefly explained an overview of about the AIMs, methods of estimation and their importance in livestock management.